Bile acid modulators for the treatment of nonalcoholic steatohepatitis (NASH). (2nd June 2020) - Fiorucci, Stefano; Biagioli, Michele; Sepe, Valentina; Zampella, Angela; Distrutti, Eleonora
ABSTRACT: Introduction: Nonalcoholic steatohepatitis (NASH) is a progressive form of nonalcoholic fatty liver disease (NAFLD) for which therapy is suboptimal. The farnesoid-X-receptor (FXR) and the G protein bile acid receptor (GPBAR)1 are two bile acid-activated receptors that exert regulatory effects on lipid, glucose, energy, and immune homeostasis. GPBAR1 and FXR ligands have shown efficacy in reversing steatohepatitis and fibrosis in preclinical models of NASH. Area covered: This article evaluates the efficacy and pitfalls of GPBAR1 and FXR-based therapies in the treatment of NASH. While there are no GPBAR1 agonist in clinical development, several FXR ligands have completed phase 2 and phase 3 trials in NASH. EDP305, tropifexor, cilofexor, nidufexor, TERN.101, Px-104, EYP001, MET409. Individual FXR agonists have shown variable efficacy in reversing liver steatohepatitis and fibrosis. Class-related, dose-dependent side effects: pruritus, increased plasma levels of cholesterol and LDLc, and reduction of HDL have been reported. Expert opinion: Efficacy of FXR agonists as stand-alone therapy is limited by dose-related side effects. Efficacy of combining an FXR agonist with statins, CCR2, and ACC inhibitors is currently investigated. Identification of patient subsets would allow development of patients tailored therapy using a combination of drugs acting on different molecular mechanisms.